OUR GREAT ANCESTOR IS INVALUABLE IN UNDERSTANDING OUR NATIONAL HISTORY THE IMPORTANCE OF SPIRITUAL AND ENLIGHTENMENT HERITAGE (Archive of Conferences, 2021)
The study of their epic in literature is an educational significance in the maturation of our youth.